Implementasi Metode MOORA Dalam Pemilihan Mahasiswa Berprestasi Dimasa Pandemi Covid-19 - Halawa, Advent; Malango, Monika Stefani; Syahrizal, Muhammad (Journal of Informatics, Electrical and Electronics Engineering, 2023)
Selection Of Outstanding Students is one of the activities usually carried out by every university or college in order to determine the level of performance of each student. In this case, the write conducts research on the Selection Of Outstanding Students with the aim of giving appreciation to students who have the best grades so that they become hope for future developments. In this study the authors use the MOORA (Multi-Objektive Optimization by Ratio Analysis) method as a Decision Support Sistem (DSS) in order to produce an objektive and accurate decision. This research was carried out during the covid-19 pandemic, which is a virus thet is hitting human health, characterized by coughs, flu, fever, no appetite, and so on. However, this condition does not rule out the possibility of students to exel, some strudents who become alternatives in the selection of outstanding students with criteria including GPA, Active Organization, Englis Ability, Achievement and warning letters. So as to produce the best reference value on alternative A3 on behalf of Viktor Zai with a value of  0.4522.